Step towards a deeper economic integration: the internal market in the 21th century. A contribution to the single market review - Ilzkovitz, Fabienne.; Dierx, Adriaan.; Kovacs, Viktoria.; Sousa, Nuno.; European Commission : Directorate-General for Economic and Financial Affairs. (European Economy. Economic papers, 2007)
The aim of this paper is to analyse the effects of the implementation of the Internal Market Programme and to propose ideas on how its potential can be better exploited. First, the paper offers a broader perspective to the analysis of the Internal Market by exploring its close links to the rapidly changing economic environment. Second, it puts together a comprehensive body of empirical evidence, based on the analysis of trade, FDI, M&A, prices and regulation data, which allows for a thorough stock taking exercise of what has been achieved in terms of European economic integration. Thirdly, it analyses the remaining barriers to the completion of the Internal Market while presenting a critical review of the adequacy of the instruments that have been used so far. Overall the paper concludes that the Internal Market is a powerful instrument to promote economic integration and to increase competition within the EU and that it has been the source of large macro-economic benefits. However, these gains could have been substantially larger if the removal of most of the remaining cross-border barriers was achieved.